Cerebrospinal fluid interleukin-6 is a potential diagnostic biomarker for central nervous system involvement in adult acute myeloid leukemia - Gu, Jiayan; Huang, Xin; Zhang, Yi; Bao, Chenhui; Zhou, Ziyang; Tong, Hongyan; Jin, Jie (Frontiers in Oncology, 2022)
Objective We evaluated the correlation between cerebrospinal fluid (CSF) cytokine levels and central nervous system (CNS) involvement in adult acute myeloid leukemia (AML). Methods The study sample consisted of 90 patients diagnosed with AML and 20 with unrelated CNS involvement. The AML group was divided into two sub-groups: those with (CNS+, n=30) and without CNS involvement (CNS-, n=60). We used a cytometric bead assay to measure CSF interleukin (IL)-2, IL-4, IL-6, and IL-10, tumor necrosis factor-α, interferon-γ, and IL-17A. We used receiver operating characteristic curves to evaluate the ability of CSF cytokine levels to identify CNS involvement in adult AML. Results CSF IL-6 levels were significantly higher in CNS+adult AML patients and positively correlated with the lactate dehydrogenase levels (r=0.738, p<0.001) and white blood cell (WBC) count (r=0.455, p=0.012) in the blood, and the protein (r=0.686, p<0.001) as well as WBC count in the CSF (r=0.427, p=0.019). Using a CSF IL-6 cut-off value of 8.27 pg/ml yielded a diagnostic sensitivity and specificity was 80.00% and 88.46%, respectively (AUC, 0.8923; 95% CI, 0.8168–0.9678). After treating a subset of tested patients, their CSF IL-6 levels decreased. Consequently, the elevated CSF IL-6 levels remaining in CNS+ adult AML patients post-treatment were associated with disease progression. Conclusion CSF IL-6 is a promising marker for the diagnosis of adult AML with CNS involvement and a crucial dynamic indicator for therapeutic response.